1974
DOI: 10.1113/jphysiol.1974.sp010661
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the hypothalamus and ovulation in the guinea‐pig

Abstract: SUMMARY1. Various methods of stimulating the hypothalamus were applied to the guinea-pig with the aim of inducing ovulation.2. Electrochemical stimulation of the hypothalamus, or gross stimulation of the brain, was ineffective.3. Electrical stimulation of the medial basal hypothalamus or rostral hypothalamus elicited gonadotrophin release.4. Despite variation of the time and intensity of stimulation, follicular luteinization was more common than the formation of new corpora lutea.5. Electrical stimulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…or oestradiol benzoate, perhaps because the implants, unlike the single injections, applied effective concentrations of the steroid to the hypothalamo-hypophysial system. Nevertheless, application of oestrogen to the hypothalamus, like electrical stimulation of that region (Booth & Donovan, 1974), still failed to induce formation of a full complement of new corpora lutea.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…or oestradiol benzoate, perhaps because the implants, unlike the single injections, applied effective concentrations of the steroid to the hypothalamo-hypophysial system. Nevertheless, application of oestrogen to the hypothalamus, like electrical stimulation of that region (Booth & Donovan, 1974), still failed to induce formation of a full complement of new corpora lutea.…”
Section: Resultsmentioning
confidence: 97%
“…While guinea-pig ovaries contain ripe follicles capable of ovulating in response to injected gonadotrophins during late dioestrus (Dempsey, Hertz & Young, 1936), it has proved difficult to elicit this response by electrical stimulation of the hypothalamus at this stage of the oestrous cycle (Booth & Donovan, 1974). In order to avoid con¬ fusion with the approaching natural ovulation, stimulation was carried out on days 10-15, before the next expected oestrus, at a time when progesterone secretion by the corpora lutea has fallen (Feder, Resko & Goy, 1968;Challis, Heap & Ulingworth, 1971), and oestrogen secretion is just beginning to rise (Joshi, Watson & Labhsetwar, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The technique of hypothalamic stimulation was based upon the work of Booth & Donovan (1974a) and the observations of Harris, Manabe & Ruf (1969), who considered that a satisfactory stimulus for the excitation of unmyelinated nerve fibres was provided by a 50 Hz alternating sine-wave current with a peak-to-peak current of 0-5-1-0 mA. Assessment of the threshold required to produce gonadotrophin release was not attempted, but it is noteworthy that the response to stimulation at 0 5 mA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(Dey, 1943; Dey, Fisher, Berry & Ranson, 1940) or surgical cuts in or around this area of the brain (Butler & Donovan,197 1). However, attempts to induce ovulation by means of electrical or electrochemical stimulation of areas of the guinea-pig brain have met with variable success (Quinn, 1969(Quinn, , 1970(Quinn, , 1974Booth & Donovan, 1974a).…”
mentioning
confidence: 99%
“…Many years ago, Dey, Fisher, Berry & Ranson (1940) showed that lesions in the anterior hypothalamus caused constant vaginal oestrus associated with highly follicular ovaries, but the changes in gonadotrophin secretion producing this effect have not been explored. However, gonadotrophin secretion in the guinea-pig is resistant to change in that electrical stimulation of the hypothalamus does not readily induce ovulation (Booth & Donovan, 1974a), and did not markedly alter the secretion ofluteinizing hormone (LH) or alter follicle-stimulating hormone (FSH) release in the spayed female (Donovan, ter Haar & Parvizi, 1977). Pre-treatment with oestrogen, progesterone or both steroids modulated the response to brain stimulation, though not to a marked degree.…”
Section: Introductionmentioning
confidence: 99%